Ganz periacetabular osteotomy: How to make the osteotomy cuts easier? - Nora Cao, MD; Ernest L. Sink, MD (Elsevier, 2024)
ABSTRACT: In 1982, Dr. Reinhold Ganz [1] introduced a new periacetabular osteotomy (PAO) as a therapeutic measure for hip dysplasia. The primary objective of this surgical procedure was the strategic reorientation of the acetabulum to optimize coverage of the femoral head and increase the surface area of the acetabular cartilage over the femoral head, all while preserving the structural integrity of the posterior column and maintaining the natural pelvic shape. The complexity of the Ganz periacetabular osteotomy presents a formidable learning curve, owing to the proximity of numerous neurovascular structures to the proposed cuts. Additionally, the surgical approach inherently lacks direct visualization of all osteotomy cuts, necessitating surgeons to rely on anatomic knowledge and meticulous interpretation of fluoroscopic views. This article endeavors to describe some techniques designed to facilitate and enhance the execution of the osteotomy. Key Concepts: (1) Superior ramus osteotomy: meticulous dissection and strategic use of retractors, such as Crego retractors, help protect obturator neurovascular structure during the superior ramus osteotomy, enabling direct visualization and precise execution of the cut. (2) Ischial osteotomy: fluoroscopic guidance aids in executing the ischial cut, with emphasis on careful consideration of sciatic nerve location, and meticulous completion of the osteotomy to prevent stress fractures into the posterior column. (3) Supra-acetabular osteotomy: creating a burr channel at the brim of the pelvic to facilitate posterior column cut later. (4) Posterior column osteotomy: performing the posterior column osteotomy involves 3 passes with a wider osteotome, regular depth checks, and an additional cut to connect the posterior column with the ischial cut.